Bilateral Retrobulbar Optic Neuritis as the First Manifestation of Neuro-Behçet Disease - Mohsen Jari; Taiiebeh Mohammadi; Ensiyeh Taheri (Case Reports in Rheumatology)
Background. Behçet disease (BD) is a polygenic and chronic autoinflammatory multisystem vasculitis. Acute optic neuritis has been rarely reported in patients with BD, especially in children. Case Presentation. We reported an 8-year-old girl with a sudden visual loss and color vision impairment. The patient had a history of recurrent oral aphthous ulcers, genital ulcers, and chronic abdominal pain. On ophthalmic examination, anterior and posterior chambers and funduscopy of both eyes were normal. The results of laboratory tests for infectious and rheumatic diseases were normal. Brain magnetic resonance imaging and the result of cerebrospinal fluid analysis for oligoclonal bands and auto-antibodies were also normal. Pathergy skin test and human leukocyte antigens (HLA) B5 and HLA-B51 were positive. The patient was recognized as a case of BD-related bilateral retrobulbar optic neuritis and was treated by corticosteroids, azathioprine, colchicine, and infliximab. Conclusion. Retrobulbar optic neuritis may be the first manifestation of neuro-BD.